Bosanc, čefur, Izbrisani. Imigrant z byłych republik jugosłowiańskich w słoweńskim filmie fabularnym - Guštin, Maša (Zagadnienia Rodzajów Literackich, 2022)
From the 1960s to the present day, immigrants have come to Slovenia mainly from the republics/ countries of the former Yugoslavia. Their appearance in Slovenian society caused a sense of threat to their own culture. Mutual relations between Slovenes and newcomers were determined from the very beginning by cultural and linguistic barriers that have not disappeared to this day. The film did not remain indifferent to this situation. The plots of the few films made between 1965 and 2018 deal with the topic of immigrants and their functioning in Slovenian society, primarily criticizing the intolerant attitude of the hosts. Using stereotypical representations of immigrants and Slovenes, they playfully or tragically emphasize inequalities in their relations, as well as the privileged position of some and the marginalization of others. Although Slovenia is widely recognized as a country open to multiculturalism, which identifies itself with the European values of respect for every individual and respect for basic human rights, the films presented create a crack in this image, showing Slovenes as an intolerant, even xenophobic society. This reluctance towards a stranger, however, focuses only on newcomers from other countries of the former Yugoslavia, who seem to be seen as a collective with unequivocally negative characteristics.